Basic human anatomy : an essential visual guide for artists - Osti, Roberto (New York, New York : Monacelli Studio, 2016)
Basic Human Anatomy teaches artists the simple yet powerful formula artists have used for centuries to draw the human figure from the inside out. Osti, using the basic system of line, shape, and form used by da Vinci, Raphael, and Michelangelo, takes readers step-by-step through all the lessons needed in order to master this essential foundation skill. Organized progressively, the book shows readers how to replicate the underlying structure of the body using easy-to-understand scales and ratios; conceptualize the front and side views of the skeleton with basic shapes; add detail with simplified depictions of complex bones and joints; draw a muscle map of the body with volumetric form and realistic dimension; master the feet, hands, and skull to create realistic renderings of the human form; and apply a deeper knowledge of anatomy to finished drawings for more impact.
Foreword / Peter Drake -- Introduction -- Drawing the figure : Keep an anatomy sketchbook -- The stereometric approach to anatomy : Proportions of the head ; Using forms that are more organic ; Landmarks of the body ; Practical benefits of the stereometric approach ; Drawing the figure : Do gesture drawings -- The structural skeleton : Proportions of the structural skeleton ; Alignment of the segments of the body ; Anatomical terminology ; Structural analysis of skeleton segments ; Drawing the figure: Use ink or watercolor washes -- Organic forms of the skeleton : Bone structures ; The whole skeleton ; Landmarks of the skeleton ; Types of bones ; The axial and appendicular skeletons ; Drawing the figure : Use a blending stump -- The muscles : Skeletal and muscular structures ; Analysis of muscles and muscle groups ; Transforming schematic volumes into organic muscle forms ; Individuating muscles by color-coding ; Drawing the figure : Mix tone and line -- The head and neck : Facial proportions and planes ; The skull ; The bones of the skull ; Muscles of the head and neck ; The neck ; Identifying facial characteristics and capturing a likeness ; Drawing the figure : Draw foreshortened and unusual poses -- The hands and feet : Proportions and shapes of the hands ; Proportions and shapes of the feet ; Drawing the figure : Draw without measuring -- Drawing techniques : Light on the form ; Tonal drawing-the trois crayons technique ; measuring and foreshortening ; Drawing the figure : Draw different body types.
Includes bibliographical references (page 302) and index.
Keywords: Anatomy, Artistic; Human figure in art